2017
DOI: 10.1103/physrevb.96.184505
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity and the isotope effect in superconducting lithium at high pressures: A first-principles approach

Abstract: Recent experiments1 have shown that lithium presents an extremely anomalous isotope effect in the 15-25 GPa pressure range. In this article we have calculated the anharmonic phonon dispersion of 7 Li and 6 Li under pressure, their superconducting transition temperatures, and the associated isotope effect. We have found a huge anharmonic renormalization of a transverse acoustic soft mode along ΓK in the fcc phase, the expected structure at the pressure range of interest. In fact, the anharmonic correction dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our observations may help explain the significant discrepancies that exist in the literature regarding the Li melting curve [7,44] and the reportedly large isotopic effect on T c between 6 Li and 7 Li [8]. It should be noted that a subsequent theoretical study has been unable to reproduce the reported effect [46].…”
mentioning
confidence: 64%
“…Our observations may help explain the significant discrepancies that exist in the literature regarding the Li melting curve [7,44] and the reportedly large isotopic effect on T c between 6 Li and 7 Li [8]. It should be noted that a subsequent theoretical study has been unable to reproduce the reported effect [46].…”
mentioning
confidence: 64%
“…The isotope effect generally occurs in a certain phase transition system, which is primarily linked to the factors including the zero-point energy, amplitude of characteristic vibrations, electron–phonon coupling, and tunneling effects . Extensive research attention has been devoted to both the normal and inverse isotope effects in superconductors, , hydrogen-bonded ferroelectrics/antiferroelectrics, and other types of phase transition crystals ,, owing to the phenomena facilitated by the phonon-assisted process.…”
Section: Introductionmentioning
confidence: 99%
“…The isotope effect generally occurs in a certain phase transition system, which is primarily linked to the factors including the zero-point energy, amplitude of characteristic vibrations, electron–phonon coupling, and tunneling effects . Extensive research attention has been devoted to both the normal and inverse isotope effects in superconductors, , hydrogen-bonded ferroelectrics/antiferroelectrics, and other types of phase transition crystals ,, owing to the phenomena facilitated by the phonon-assisted process. In contrast, within magnetic phase transition materials, the isotope effect has only been observed in a limited number of phonon-assisted phase transition systems, such as spin crossover , and spin-Peierls systems, , up to the present time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a stochastic implementation of the SCHA method has been developed to study the equilibrium crystal structure and phonon band structure of real anharmonic materials from first principles [16][17][18][19]. This method has been successfully applied to various lattice-related phenomena such as structural phase transitions [18][19][20][21], superconductivity [16,[22][23][24][25], and charge density waves [26][27][28][29][30][31] and to the dynamical properties such as the phonon spectral function [20,21,[32][33][34] and infrared and Raman spectra [35].…”
mentioning
confidence: 99%